The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2310/7750.2014.14076
|View full text |Cite
|
Sign up to set email alerts
|

Low Glutathione Peroxidase Activity Levels in Patients with Vitiligo

Abstract: Low levels of serum GPx activity, indicative of a disturbed oxidant-antioxidant system, may contribute to the development of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…In the present study, we initially found that EGb761 showed no toxic effect on PIG1 cells (data not shown), which was consistent with previous studies . The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH‐Px . Our study showed that EGb761 could significantly restore the activity of SOD and GSH‐Px in PIG1 cells under H 2 O 2 treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we initially found that EGb761 showed no toxic effect on PIG1 cells (data not shown), which was consistent with previous studies . The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH‐Px . Our study showed that EGb761 could significantly restore the activity of SOD and GSH‐Px in PIG1 cells under H 2 O 2 treatment.…”
Section: Discussionsupporting
confidence: 93%
“…10 The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH-Px. 20,21 Our study showed that EGb761 could significantly restore the activity of SOD and GSH-Px in PIG1 cells under H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 70%
“…[ 4 ] Furthermore, decrease in the antioxidant enzyme glutathione peroxidase levels has been observed in the sera of vitiligo patients. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data have been reported about GPx levels in vitiligo patients, with a recent meta-analysis finding that GPx levels were decreased in Asian, but not white, vitiligo patients (Xiao et al, 2016). However, a study of 60 vitiligo patients found decreased GPx activity levels when compared with control subjects and a statistically significant decrease in GPx in patients with dark skin phenotypes (skin types IV and V) when compared with lighter skin types (skin type III) (Zedan et al, 2015). Thus, lower levels of GPx in women with darker skin phenotypes, which would include those with increased tanning ability, may confer a greater vitiligo risk.…”
mentioning
confidence: 99%